The Influence of Live Streaming and Content Marketing on Gen Z's Purchase Intention: The Mediating Role of Trust in Tiktok Live in South Lampung - Radiansyah, Egi; Listiana, Melda (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: The development of digital technology has driven changes in marketing strategies, one of which is through the TikTok platform, now utilized as an interactive promotional medium. TikTok has evolved from an entertainment platform into an effective digital marketing tool through its live streaming and content marketing features, which are capable of influencing consumers' purchase intentions.Purpose: This study aims to investigate the influence of live streaming and content marketing on purchase intention and to examine the mediating role of trust TikTok Live was selected due to its popularity among Gen Z and its interactive features that make it ideal for studying consumer behavior among TikTok Live consumers in South Lampung.Design/methodology/approach: This research adopts a quantitative approach. The sample consists of 200 respondents. Data were collected through an online questionnaire distributed to individuals who had previously made purchases via TikTok Live. Respondents were selected using purposive sampling technique. Data analysis was conducted using the SEM-PLS method with the assistance of SMART-PLS 4 software.Findings: The results reveal that live streaming (path coefficient = 0.543) and content marketing (path coefficient = 0.343) significantly influence purchase intention. Trust significantly mediates both relationships. Consumers tend to be more inclined to make purchases after engaging directly through live streaming or after being exposed to relevant and engaging marketing content. Additionally, trust is proven to mediate the relationship between live streaming and content marketing on purchase intention, indicating that consumer trust is a crucial factor in strengthening the influence of these marketing strategies on purchase decisions. This finding suggests that the higher the consumer trust toward the live streamer and the presented content, the higher their intention to purchase.Conclusion: This study provides a novel contribution by emphasizing the pivotal role of trust as a mediating factor in live streaming-based marketing strategies targeting Gen Z. The findings deepen the understanding of how trust enhances the effectiveness of digital marketing efforts, particularly in the context of live commerce platforms like TikTok Live.Originality/value: This study offers a new contribution to digital marketing research by integrating trust as a mediating variable between live streaming and content marketing on purchase intention on the TikTok Live platform. It broadens the understanding of how interactive features and creative content on social media can build consumer trust and drive purchasing intention. Additionally, the research provides practical insights for e-commerce companies and business actors in designing more effective social media marketing strategies, emphasizing the importance of managing interaction and content credibility to optimize marketing outcomes via TikTok Live. Keywords: live streaming, content marketing, purchase intention, consumer behavior, TikTok live